DETERMINANT FACTORS FOR SUCCESS OF CORPORATE GOVERNANCE IN AN ORGANIZATION (Singaporean Journal of Business Economics and Management, 2013)
The discourse on corporate governance can become conceptual and scientific beyond the reach of the ordinary investor and the larger society. It is vital that the language of corporate governance be understood by the ordinary investor who may not have a finance degree. There is the need for corporate governance to move from mount Olympus of the boardroom to the valley of the ordinary investor. This will ensure a stronger shareholder voice and better governance of our institutions. In this paper we will examine the factors that determine the success of the quality of corporate governance of an organization.